Healthcare Data Privacy Protection Through the Lens of Big Data - Pan, Yuexin (International Journal of Computer Science and Information Technology, 2024)
In the era of rapid development of big data, there are more and more fields that have a close connection with big data technology, of which the medical field is a particularly important part. Nowadays, citizens reflect that the medical information they had uploaded to the cloud platform has been leaked frequently, even in some regular hospitals and other government-provided platforms, which has aroused citizens’ doubts and dissatisfaction. This paper will combine the two perspectives of the field of medical information and big data technology to provide new countermeasures and solutions for solving the problem of medical data leakage from the perspective of big data technology and combining with citizens’ awareness of privacy protection.